EFEKTIVITAS PROGRAM LAYANAN TERPADU ADMINDUK (LANTERA) DALAM PELAYANAN E-KTP DI KABUPATEN KUANTAN SINGINGI TAHUN 2022-2024 - Muliawan, Muhammad Arif; Rafi, M. (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2025)
This study aims to examine the effectiveness of the Integrated Population Administration Service Program (Lantera) in providing e-KTP services in Kuantan Singingi Regency in 2022-2024. The Lantera program was initiated as an innovation to improve access to population administration services, particularly for residents in remote areas. A descriptive method with a qualitative approach was used. Data were collected through interviews, observations, and documentation using purposive sampling techniques. The findings indicate that the Lantera program has had a positive impact in accelerating the recording and issuance of e-KTPs, as evidenced by a decrease in the number of unfulfilled e-KTP obligations from year to year: 10,676 (2022), 7,416 (2023), and 4,852 (2024). The e-KTP ownership rate also increased from 95.70% (2022) to 97.10% (2023), and further to 98.17% (2024). However, the program has not yet reached full optimization due to challenges such as limited network access, low public understanding of procedures, and inconsistent service hours. Overall, the Lantera program can be considered fairly effective in achieving its goal of expanding the coverage of population administration services. Keywords: Program Effectiveness, Lantera, e-KTP, Population Administration.